The Use of Interactive Flat Panel (IFP) Technology as a Medium for Strengthening Social Interaction in Learning at SMPN Ma'arif 1 Ponorogo - Fatimah Az zahrah Nurrohmah; Husein Al-Haedar Saddad; Susika Asgia Permaidani (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
Interactive Flat Panel (IFP) technology is a digital learning innovation that not only functions as a medium for delivering material, but also as a means of strengthening social interaction in the learning process. This study was motivated by the limited social interaction among junior high school students in conventional learning, which has resulted in low participation, cooperation, and communication among students. This study aims to describe and analyze the use of IFP technology in strengthening student social interaction through interactive learning activities such as class discussions, group work, presentations, and collaborative quizzes. The research used a descriptive approach with interpretive analysis of questionnaire data given to students at SMPN Ma'arif 1 Ponorogo. The results showed that the use of IFP was able to increase the intensity of social interaction, both between students and between students and teachers, especially through collaboration-based and gamification activities. However, there were still technical obstacles and limitations in the teachers' competence in optimizing the IFP function. This study confirms that the appropriate use of IFP can be a strategic tool in strengthening student social interaction and supporting collaborative and learner-centered learning.